Nurses’ perceived difficulties in preoperative patient preparation: a qualitative study - Gonçalves, Marco; Pereira, Maria Aurora; Machado, Natália (Millenium - Journal of Education, Technologies, and Health, 2024)
Introduction: The role of the nurse in the preoperative period involves identifying the client's needs and the risk factors related to the entire perioperative period. This preoperative preparation is not always a straightforward process and has some challenges that are important to explore in order to highlight the autonomous intervention of nurses during this period. Objective: To explore the difficulties perceived by nurses in the preoperative preparation of clients undergoing scheduled general surgery. Methods: An exploratory, qualitative study was carried out. To collect data, 23 semi-structured interviews were carried out with nurses who had been working in operating theatres or general surgery departments for more than 5 years. The data was analyzed using Bardin's content analysis technique. Results: Three thematic units emerged from the content analysis: difficulties experienced, contributions of the preoperative nursing consultation, and aspects to be taken into account when organizing the consultation. The difficulties mentioned by the nurses centered on the preparation of the surgical client and the conditions for this preparation. Conclusion: Identifying nurses' perceptions of the preoperative preparation that is currently carried out for clients undergoing scheduled general surgery made it possible to find out about the difficulties they experience. Preoperative preparation should be structured and take into account various dimensions such as physical, emotional, knowledge and logistical aspects. These results will contribute to improving the nursing care provided during the perioperative period.